Korelasi Agama dan Negara dalam Bingkai Keindonesiaan - Alwaris, Sri Ayu Andari Putri; M, Mahmuddin; B, Barsihannor (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Discourse on the relationship between religion and state will always be hotly discussed in various discussions and studies. This shows how important the relationship between the two terms is. Religion is a deep belief for its adherents, but when the state does not provide a sense of security for the implementation of religious teachings, it will cause turmoil in society. Likewise, in its implementation, the state also needs the presence of religion, so that in the state it can be more orderly and directed according to religious values. So far, there have been some different understandings among Muslims regarding the relationship between religion and state. Where some assume that the issue of religion and state cannot be united in its implementation, this is what is practiced by some countries that consider religion and state to be separated (secular understanding). Likewise, there are those who have the opinion that religion is not only a dogma, but religion provides a foundation for reconstructing the system or values of religion in building the state.